Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

dana.lindsey

  • 3 years ago

Which equation will result if the substitution method is used to solve the following system of linear equations? x + y = 6 x = y - 2 (y - 2) + y = 6 x + y = y - 2 x + (y - 2) = 6 x = (x - 6) - 2

  • This Question is Open
  1. Phyzix
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    If x is substituted in, you would get (y-2) + y = 6.

  2. FoolForMath
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 3

    x + y = 6 --- (1) x = y - 2 ----( 2) Substituting (2) in (1): (y - 2) + y = 6

  3. KukoRamos
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    x+y=6 x-y=-2 2x =4 x =2 y =4 (2,4)

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy